Association between longitudinal clinical outcomes in patients with hip fracture and their pre‐fracture place of residence. Issue 1 (28th March 2019) - Balzer‐Geldsetzer, Monika; Buecking, Benjamin; Ruchholtz, Steffen; Kis, Bernhard; Dodel, Richard; Hessmann, Philipp
Abstract : Background: Clinical outcomes of patients with proximal femoral fracture within 1 year after hospitalization are presented. In particular, associations between the patients' clinical status and their pre‐fracture residence were evaluated (community‐dwelling vs nursing home). Methods: Patients aged ≥60 years with proximal femoral fractures were included in a prospective, single‐centre observational study and followed for 12 months. Patients' clinical status at baseline was compared to their health status at follow‐up 12 months later. Several standardized questionnaires were used to evaluate the patients' functional and cognitive capacity (e.g. Lawton Instrumental Activities of Daily Living Scale, Barthel Index, and Mini‐Mental State Examination), mobility (timed up‐and‐go test, Tinetti Test, and Harris Hip Score), quality of life (EuroQol‐5 Dimensions index and EuroQol Visual Analogue Scale), and psychological status (Geriatric Depression Scale). Results: This study included 402 patients (mean age: 81.3 ± 8.2 years, 72% women). Patients stayed in hospital for 13.7 ± 6.1 days on average. The comparison of patients' clinical status at baseline and at 12‐month follow‐up revealed that the Mini‐Mental State Examination and Charlson Comorbidity Index remained unchanged ( P = 0.527 and P = 0.705), the level of depression (Geriatric Depression Scale) significantly decreased ( P < 0.001), and quality of life (EuroQol‐5 Dimensions index) diminished ( P < 0.001). Although patients' mobility increased after 12 months ( P < 0.001 for timed up‐and‐go test and Harris Hip Score), their functional capacity was significantly reduced ( P < 0.001 for Barthel Index and Lawton Instrumental Activities of Daily Living Scale). Nursing home residents showed a significantly higher impairment at baseline than community‐dwelling individuals and less improvement in functional and cognitive tests at 12‐month follow‐up. Conclusions: Clinical outcomes after hip fracture are significantly associated with patients' pre‐fracture residence status. Place of residence as well as functional and cognitive status on admission may lead to differences in functional recovery and affect therapeutic and rehabilitative decision‐making.